Non-specific gastrointestinal features: Could it be Fabry disease? - Hilz, Max-Josef; Arbustini, Eloisa; Dagna, Lorenzo; Gasbarrini, Antonio; Goizet, Cyril; Lacombe, Didier; Liguori, Rocco; Manna, Raffaele; Politei, Juan; Spada, Marco; Burlina, Alessandro (Digestive and Liver Disease, 2018)
Non-specific gastrointestinal symptoms, including pain, diarrhoea, nausea, and vomiting, can be the first symptoms of Fabry disease. They may suggest more common disorders, e.g. irritable bowel syndrome or inflammatory bowel disease. The confounding clinical presentation and rarity of Fabry disease often cause long diagnostic delays and multiple misdiagnoses. Therefore, specialists involved in the clinical evaluation of non-specific upper and lower gastrointestinal symptoms should recognize Fabry disease as a possible cause of the symptoms, and should consider Fabry disease as a possible differential diagnosis. When symptoms or family history suggest Fabry disease, in men, low alpha-galactosidase A enzyme levels, and in women, specific Fabry mutations confirm the diagnosis. In addition to symptomatic treatments, disease-specific enzyme replacement therapy with recombinant human alpha-galactosidase A enzyme or chaperone therapy (migalastat) in patients with amenable mutations can improve the disease, including gastrointestinal symptoms, and should be initiated as early as possible after Fabry disease has been confirmed; starting enzyme replacement therapy at as young an age as possible after diagnosis improves long-term clinical outcomes. Improved diagnostic tools, such as a modified gastrointestinal symptom rating scale, may facilitate diagnosing Fabry disease in patients with gastrointestinal symptoms of unknown cause and thus assure timely initiation of disease-specific treatment.
EVALuna2:201940